2019
DOI: 10.1038/d41586-019-00763-0
|View full text |Cite
|
Sign up to set email alerts
|

Support smallholders to step up Nigeria’s cassava yields

Abstract: Danish children find new bacteria One of the worlds' largest citizenscience experiments has led to the rapid discovery of ten new bacterial species in Denmark. About 25,000 schoolchildren aged 10-16 years found these Lactobacillus species after analysing some 11,000 plant samples from urban and rural ecosystems (see go.nature. com/2sq5muw). By comparison, Danish researchers find an average of just one new bacterial species per year. Lactobacillus is a beneficial group of bacteria that has been used for food pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Recombinant MeHSP90.9-Myc protein was immunoprecipitated using anti-Myc antibody, and the co-immunoprecipitated XopC2-Flag protein was assayed using anti-Flag antibody, respectively. Ó 2024 The Authors New Phytologist Ó 2024 New Phytologist Foundation identified disease resistance genes and disease-resistant cassava germplasms are very limited (Maxmen, 2019;Nitturkar, 2019). Here, we clarify the function of MeHSP90.9 protein phosphorylation in promoting cassava immune responses and reveal the dual roles of MeHSP90.9 in cassava-bacterial pathogen interaction.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Recombinant MeHSP90.9-Myc protein was immunoprecipitated using anti-Myc antibody, and the co-immunoprecipitated XopC2-Flag protein was assayed using anti-Flag antibody, respectively. Ó 2024 The Authors New Phytologist Ó 2024 New Phytologist Foundation identified disease resistance genes and disease-resistant cassava germplasms are very limited (Maxmen, 2019;Nitturkar, 2019). Here, we clarify the function of MeHSP90.9 protein phosphorylation in promoting cassava immune responses and reveal the dual roles of MeHSP90.9 in cassava-bacterial pathogen interaction.…”
Section: Discussionmentioning
confidence: 83%
“…In recent decades, CBB has become one of the most serious global cassava diseases (Bart & Taylor, 2017;Mccallum et al, 2017;Maxmen, 2019;Nitturkar, 2019). However, the current Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations